Neuroendodermal cyst in the fourth ventricle of a dog. Issue 8 (27th July 2017) - Kent, M; Glass, EN; Miller, AD; de Lahunta, A
Abstract : Case report: We describe the MRI appearance and surgical outcome of a rare neuroendodermal cyst in the fourth ventricle of a German Shorthaired Pointer. The dog presented with uncoordinated gait and occasional falling that increased when she became excited. The MRI appearance is shown and the surgical treatment described. Recurrence occurred on two occasions and the dog was euthanased. Conclusion: Recurrence of these cysts is highly likely unless there is complete surgical resection.